Bifidobacterium infantis Promotes Foxp3 Expression in Colon Cells via PD-L1-Mediated Inhibition of the PI3K-Akt-mTOR Signaling Pathway - Zhou, Linyan; Xie, Ying; Li, Yan (Frontiers in Immunology, 2022)
Aim: Our objective was to investigate whether Bifidobacterium infantis inhibits PI3K-Akt-mTOR signaling and upregulates Foxp3 expression through PD-L1 and to explore the possible mechanism of action of B. infantis in cellular immunosuppression. Method: The effects of B. infantis supernatant on PD-L1, PD-1, Foxp3, and the PI3K-Akt-mTOR signaling pathway were observed by culturing HCT-116 cells. Simultaneously, the effects of blocking PD-L1 on PD-1, on Foxp3 protein and mRNA, and on the PI3K-Akt-mTOR signaling pathway protein were observed. Results: B. infantis supernatant was able to upregulate the protein and mRNA expression of PD-L1 and Foxp3 and downregulate the phosphorylated protein expression of PI3K, Akt, and mTOR (P < 0.05); however, for PI3K, Akt, and mTOR, there was no change in the total protein expression. After the blocking of PD-L1, the stimulatory effect of B. infantis supernatant on Foxp3 and the inhibitory effect on the phosphorylated protein expression of PI3K, Akt, and mTOR were weakened. Conclusion: B. infantis may inhibit the PI3K-Akt-mTOR signaling pathway and promote the expression of Foxp3 through PD-L1, which may be a target via which B. infantis exerts its immunosuppressive effect.